The Effect of Tong-Xie-Yao-Fang on Intestinal Mucosal Mast Cells in Postinfectious Irritable Bowel Syndrome Rats. (26th February 2017) - Ma, Xiangxue; Wang, Xiaoge; Kang, Nan; Chen, Ting; Ji, Haijie; Lv, Lin; Yin, Xiaolan; Tian, Yaxin; Zheng, Rui; Duan, Yuanzhi; Wang, Fengyun; Tang, Xudong
Abstract : Objective . To investigate the effects of Tong-Xie-Yao-Fang (TXYF) on intestinal mucosal mast cells in rats with postinfectious irritable bowel syndrome (PI-IBS). Design . PI-IBS rat models were established using a multistimulation paradigm. Then, rats were treated with TXYF intragastrically at doses of 2.5, 5.0, and 10.0 g·kg −1 ·d −1 for 14 days, respectively. Intestinal sensitivity was assessed based on abdominal withdrawal reflex (AWR) scores and fecal water content (FWC). Mast cell counts and the immunofluorescence of tryptase and c-Fos in intestinal mucosa were measured; and serum IL-1 β, TNF- α, and histamine levels were determined. Results . AWR reactivity and FWC which were significantly increased could be observed in PI-IBS rats. Remarkably increased mast cell activation ratio in intestinal mucosa, together with increased serum TNF- α and histamine levels, could also be seen in PI-IBS rats; furthermore, PI-IBS-induced changes in mast cell activation and level of serum TNF- α and histamine could be reversed by TXYF treatment. Meanwhile, tryptase and c-Fos expression were also downregulated. Conclusion . TXYF improves PI-IBS symptoms by alleviating behavioral hyperalgesia and antidiarrhea, the underlying mechanism of which involves the inhibitory effects of TXYF on activating mucosal mast cells, downregulating tryptase and c-Fos expression, and reducing serum TNF- α and histamine levels.